The Insight Evaluation Approach - Craig Russon; Karen Russon (The Evaluation Center at Western Michigan University, 2009)
Projects and programmes that are often the objects of our inquiry are actually no more than mental constructs. They are the result of numerous conditions that happen to come together for one brief moment. Their funding, activities, and results arise, dwell in a state of constant flux for a period of time, and then pass away. Insight Evaluation provides an approach to see projects and programmes clearly, without false impression. The views expressed in this manuscript are those of the authors and do not necessarily reflect the policy of the International Labour Organization, the United Nations, or the Evaluation Capacity Development Group